Synthesis and insecticidal activities of novel solanidine derivatives. Issue 3 (3rd October 2018) - Beaulieu, Rémi; Grand, Eric; Stasik, Imane; Attoumbré, Jacques; Chesnais, Quentin; Gobert, Virginie; Ameline, Arnaud; Giordanengo, Philippe; Kovensky, José
Abstract: Background: Potato ( Solanum tuberosum ) is the fourth culture in the world and is widely used in the agri‐food industries. They generate by‐products in which α‐chaconine and α‐solanine, the two major solanidine‐based glycoalkaloids of potato, are present. As secondary metabolites, they play an important role in the protection system of potato and are involved in plant protection against insects. To add value to these by‐products, we described here new glycoalkaloids that could have phytosanitary properties. Results: Solanidine, as a renewable source, was modified with an azido linker and coupled by copper‐catalyzed alkyne azide cycloaddition to alkynyl derivatives of the monosaccharides found in the natural potato glycoalkakoids:D ‐glucose, D ‐galactose and L‐rhamnose. The efficacy of our compounds was evaluated on the potato aphid Macrosiphum euphorbiae . The synthetic compounds have stronger aphicidal properties against nymphs than unmodified solanidine. They also showed strong aphicidal activities on adults and a negative impact on fecundity. Conclusion: Our synthetic neoglycoalkaloids affected Macrosiphum euphorbiae survival at the nymphal stage as well as at the adult stage. Furthermore, they induced a decrease in fecundity. Our results show that chemical modifications of by‐products may afford new sustainable compounds for crop and plant protection. © 2018 Society of Chemical Industry Abstract : This article describes the synthesis of new glycoalkaloids starting from potato solanidine. The synthetic neoglycoalkaloids showed aphicidal activities against Macrosiphum euphorbiae nymphs and adults.